Epigenetic regulation of Fructose‐1, 6‐bisphosphatase 1 by host transcription factor Speckled 110 kDa during hepatitis B virus infection. (25th June 2022) - Sengupta, Isha; Mondal, Payel; Sengupta, Amrita; Mondal, Atanu; Singh, Vipin; Adhikari, Swagata; Dhang, Sinjini; Roy, Siddhartha; Das, Chandrima
Abstract : Hepatitis B virus (HBV) is the leading cause of liver disease ranging from acute and chronic hepatitis to liver cirrhosis and hepatocellular carcinoma (HCC). Studies have revealed that HBV infection broadly reprogrammes the host cellular metabolic processes for viral pathogenesis. Previous reports have shown that glycolysis and gluconeogenesis are among the most deregulated pathways during HBV infection. We noted that despite being one of the rate‐limiting enzymes of gluconeogenesis, the role and regulation of Fructose‐1, 6‐bisphosphatase 1 (FBP1) during HBV infection is not much explored. In this study, we report FBP1 upregulation upon HBV infection and unravel a novel mechanism of epigenetic reprogramming of FBP1 by HBV via utilizing host factor Speckled 110 kDa (Sp110). Here, we identified acetylated lysine 18 of histone H3 (H3K18Ac) as a selective interactor of Sp110 Bromodomain. Furthermore, we found that Sp110 gets recruited on H3K18Ac‐enriched FBP1 promoter, and facilitates recruitment of deacetylase Sirtuin 2 (SIRT2) on that site in the presence of HBV. SIRT2 in turn brings its interactor and transcriptional activator Hepatocyte nuclear factor 4‐alpha to the promoter, which ultimately leads to a loss of DNA methylation near the cognate site. Interestingly, this Sp110 driven FBP1 regulation during infection was found to promote viral‐borne HCC progression. Moreover, Sp110 can be used as a prognostic marker for the hepatitis‐mediated HCC patients, where high Sp110 expression significantly lowered their survival. Thus, the epigenetic reader protein Sp110 has potential to be a therapeutic target to challenge HBV‐induced HCCs. Abstract : Sp110, a PML body protein, recognizes H3K18Ac marks at the promoter of gluconeogenic gene FBP1 and facilitates recruitment of deacetylase Sirtuin2 and Hepatocyte nuclear factor 4‐alpha on the site in presence of hepatitis B virus. These factors lead to an alteration of epigenetic landscape near the cognate site and ultimately promote transcriptional activation of FBP1 . This Sp110‐mediated metabolic regulation during infection has a direct consequence in viral‐borne hepatocellular carcinoma.